2014
DOI: 10.4025/actascianimsci.v36i3.22839
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of estradiol-17β on the sex ratio, growth and survival of juvenile common snook (<i>Centropomus undecimalis</i>)

Abstract: ABSTRACT. Sex control in fish is a promising technique for aquaculture, since it gives advantages associated with one sex. The aim of this study was to investigate the feminization of common snook (Centropomus undecimalis) by oral administration of two doses of estradiol-17β (50 and 100 mg E 2 kg -1 feed) and control treatment for 45 days and to evaluate their effects on the sex ratio, growth and survival of common snook juveniles. After this period, fish were fed only with commercial feed without hormone supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In the presently reported study, fish groups fed E 2 had no significant changes in growth parameters, which is in agreement with the results studied on Amatitlania nigrofasciata (see George and Pandian 1996) and Centropomus undecimalis (see Carvalho et al 2014). Similarly, studies on Xiphophorus helleri by Lim et al (1992) and Tamaru et al (2009) stated that the hormones did not have any adverse effect on the growth.…”
Section: Discussionsupporting
confidence: 90%
“…In the presently reported study, fish groups fed E 2 had no significant changes in growth parameters, which is in agreement with the results studied on Amatitlania nigrofasciata (see George and Pandian 1996) and Centropomus undecimalis (see Carvalho et al 2014). Similarly, studies on Xiphophorus helleri by Lim et al (1992) and Tamaru et al (2009) stated that the hormones did not have any adverse effect on the growth.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, feminization of testes was observed in juvenile Chum salmon (Oncorhynchus masou), for which sex is distinguishable by 25 day post-hatch (dph), by exposing individuals to 1 µL E 2 L -1 from 34-100 dph (Nakamura, 1984). Similarly, feminization of juvenile common snook (Centropomus undecimalis) was achieved in 90% of juveniles using feed supplemented with 100 mg kg -1 E 2 for 45 days (Carvalho et al, 2014) and in 100% of 3 year old male fish implanted with exogenous E 2 (Passini et al, 2016). Recently, feminization of juvenile barramundi was achieved using commercial pellets supplemented by 20 mg E 2 kg -1 feed from 30 -120 dph (Banh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [29] found that E 2 had a negative effect on the growth of small yellow croaker (Larimichthys polyactis). Cravalho et al [30] showed that 50 and 100 mg•kg −1 E 2 had an inhibitory effect on the body length and body mass of common snook (Centropomus undecimalis). Blazquez et al [31] found that E 2 inhibited the growth of body mass in sea bass (Dicentrarchus labrax).…”
Section: Discussionmentioning
confidence: 99%